Think-Talk-Write Strategy to Improve the Ability to Compose Indonesian Sentence Structure in SLBN Cicendo Bandung, Indonesia - Endang Rusyani; Shintiya Erni Karyana; Budi Susetyo; Silmi Ridwan Putri (Indonesian Journal of Educational Research and Technology, 2021)
This study aims to see whether the Think-Talk-Write method improves deaf children's capacity to compose Indonesian language sentence structures. The research method used was an experimental method using the design of one group pretest-posttest. The data collection technique used was a writing test. This study was conducted on seven deaf children in class XI at special needs school in Cicendo, Bandung, Indonesia. The study's findings based on the comparison of pre-test and post-test scores showed an increase in post-test scores was higher in each aspect, namely in the elements of Think, Talk, and Writes. This evidence showed that the seven subjects being able to choose random words and then arrange the words into a sentence structure with the subject-verb-object sentence pattern. This research can be a recommendation for teachers regarding the use of learning strategies, especially the Think-Talk-Write strategy to help improve the ability to compose Indonesian sentence structures or other materials for deaf children.